Training Website and E-Commercen Tokotalk PKK and MSMEs Pagertanjung Village Ploso District - Faisol Hamid; Elok Virgiawati; Febi Agustina; Faiza Nur Amalia Putri (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
MSMEs can improve the community's economy. MSMEs can create community creativity and create new markets. The problem found in Pagertanjung Village, Ploso District, is that there are still at least MSMEs. The survey results state that some of them have an interest but still have not found the idea and motivation to open a business. There are also those who have no interest in opening a business because their profession is a farmer. Therefore, we provide two solutions. provides training on the creation of a TokoTalk e-commerce website. The benefit of this training is that business actors can create accounts and market their products more broadly. The public can also increase their knowledge about e-commerce, manufacture of packaging labels, and online marketing. It is hoped that this training can provide ideas and motivation for the community to open a business so that it can improve the economy of Pagertanjung Village, Ploso.